2022
DOI: 10.2196/34576
|View full text |Cite
|
Sign up to set email alerts
|

Casting Without Reduction Versus Closed Reduction With or Without Fixation in the Treatment of Distal Radius Fractures in Children: Protocol for a Randomized Noninferiority Trial

Abstract: Background Acute treatment for distal radius fractures, the most frequent fractures in the pediatric population, represents a challenge to the orthopedic surgeon. Deciding on surgical restoration of the alignment or cast immobilization without reducing the fracture is a complex concern given the remodeling potential of bones in children. In addition, the lack of evidence-based safe boundaries of shortening and angulation, that will not jeopardize upper-extremity functionality in the future, further… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this register cohort, boys (54%) more often had a fracture than girls (46%) and this trend grew stronger the older they became, which has been reported previously in both the Swedish-based study of Südow et al . [ 22 ] and other studies outside of Sweden [ 1 , 2 , 9 , 12 , 15 ]. Our results also showed that boys were more likely to acquire a complete fracture compared to girls, whereas the prevalence of a torus fracture is higher amongst girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this register cohort, boys (54%) more often had a fracture than girls (46%) and this trend grew stronger the older they became, which has been reported previously in both the Swedish-based study of Südow et al . [ 22 ] and other studies outside of Sweden [ 1 , 2 , 9 , 12 , 15 ]. Our results also showed that boys were more likely to acquire a complete fracture compared to girls, whereas the prevalence of a torus fracture is higher amongst girls.…”
Section: Discussionmentioning
confidence: 99%
“…The peak age was 10 years for girls and 12 years for boys and the mean age was 9 (SD 2) years for both sexes; previous studies show a mean age for children with a DRF ranging between 8 and 13 years [ 2 , 4 , 15 , 12 , 9 ]. In the Swedish study by Südow et al ., based on data from the Swedish National Patient Register for 2005–2013, the mean age was 10 years (range 0–17 years), more specifically 10.7 years for boys and 9.3 years for girls [ 22 ].…”
Section: Discussionmentioning
confidence: 99%